Finite cyclic q-group’s automorphisms with qr -generator - Hasan, Fatin Hanani; Mohamad, Mohd Sham; Yusof, Yuhani; Mohd Busul Aklan, Nor Amirah; Jusoo, Siti Hasanah; Sangwisut, Ekkasit (Universiti Malaysia Pahang Al-Sultan Abdullah Publishing, 2024)
The finite cyclic q-group, where q being odd prime, requires generators to validate the formation of automorphisms. A summary of cyclic groups, automorphisms, and characteristics is provided as a foundation for this research. By evaluating the automorphisms, the generators for the qr -power cyclic group in their specific sequence have been uncovered and presented as the key finding.